An era of digital slavery: a study on internet addiction among professional college students of Hassan, Karnataka - K. J., Subhashini; G., Praveen (International Journal Of Community Medicine And Public Health, 2018)
Background: The spectacular growth of technology has made Internet use, the most popular recreational and academic activity for the college students. With the rise of new-generation gadgets, the risk of “internet addiction” is a significant issue of concern. Internet addiction leads to social and psychological problems such as depression, loneliness, low self-esteem and life satisfaction and other mental health problems and a greater impact on their academics. The objective of the study was to determine the association between internet addiction and depression and to know the effect of gender on internet addiction. Methods: A cross-sectional study was carried out on the professional course students from Hassan Institute of Medical Sciences (Government Medical College) and Government Engineering College. A total of 300 students were assessed for internet addiction using Young’s internet addiction test and depression was assessed using Beck’s depression inventory-II. Results: Out of the 300 professional college students, 173 (57.7%) were found to be internet addicted and 67 (38.7%) among them were found to be depressed and a statistically significant association (p<0.05, OR 3.6, 95% CI 2.02–6.39) was found. Males were found to be more addicted than females and it was statistical significant. Conclusions: Internet Addiction is common among the college students and adequate steps have to be taken to prevent the students from falling into addiction which is considered as a mental health issue. Knowledge regarding the safe use of internet has to be provided to students.